Pengaruh Desentralisasi Fiskal dan Kinerja Pemerintah Daerah terhadap Akuntabilitas Pelaporan Keuangan: Studi Empiris pada Pemerintah Kabupaten/Kota di Papua Tahun 2021-2022 - Mofu, Jesse Stellani; Arza, Fefri Indra (Universitas Negeri Padang, 2025)
This study aims to examine the effect of fiscal decentralization (as proxied by regional independence, dependence on central government and effectiveness) and local government performance on financial reporting accountability in local governments in Papua for the 2021-2022 period. This research is a quantitative study using secondary data. The sampling technique used purposive sampling. The number of samples during the study year amounted to 50 data, which were analyzed using the IBM SPSS 25 application. The results showed that fiscal decentralization proxied through regional independence, dependence on central government and effectiveness had no positive effect on financial reporting accountability, but local government performance had a positive effect on financial reporting accountability in Papua in the 2021-2022 period.